MODELS OF CREEP AND RELAXATION WITH USING OF FRACTIONAL DERIVATIVES - S V Erokhin (Structural Mechanics of Engineering Constructions and Buildings, 2014)
Creep and relaxation models based on fractional derivatives are submitted. Models of parameter determination are described. It allows predicting system behavior.